Management of chronic subdural hematoma: our experience of last seven years - Nath, Amar; Fotedar, Sanjay (International Surgery Journal, 2021)
Background: Chronic SDH is collection of altered blood under dura mater which is variably more than 4-6 weeks old. It usually occurs in presence of atrophic brain which usually occurs in chronic alcoholics and in old age. Pathogenetic factors are mild trauma with or without some form of coagulopathy. There are various management options like twist drill and drainage, burr hole with evacuation with or without placement of drain and mini craniotomy. There are specific indications for each procedure with individual variations. We operated 74 patients of chronic SDH in last 7 years and are presenting analysis of our series. Methods: The study is retrospective. We studied records of 74 consecutive patients operated in single unit at our institute from February 2014 to December 2020. Patients with very poor GCS (less than 5) and children are not included in this study. Results: There was no benefit of drainage tube seen in our series of patients in decreasing incidence of residual collection. Conclusions: Timely intervention in case of chronic SDH is very gratifying in view of improvement of GCS and motor deficit without much effect of the type of procedure performed. Burr hole evacuation is the procedure of choice. Placement of drainage tube in subdural space is not effective in decreasing the incidence of residual collection. But it is very helpful in management of residual/recurrent collections.